Recycling waste tire into concrete-rubber composite - Mokhzani Khair, Ishak; Khairul Nizar, Ismail; Kamarudin, Hussin; Wan Mohd Sabki, Wan Omar; Mohd Asri, Ab. Rahim; Umar, Kassim; Libren Francis, Doublin; Norfadhilah, Ibrahim (Universiti Kebangsaan Malaysia (UKM), 2011)
Regional Engineering Postgraduate Conference 2009 (EPC 2009) organized by Faculty of Engineering & Built Environment, Universiti Kebangsaan Malaysia from 20th - 21st October 2009 at Palm Garden Hotel, Putrajaya, Malaysia.